Preparation and Application Progress of Starch-Based Hydrogels - Andersson, Sven; Kim, Natalie; Gupta, Rajesh (Journal of Green Energy and Environmental Engineering, 2023)
Hydrogels are polymeric materials with a three-dimensional network structure formed via the crosslinking of hydrophilic polymer chains, exhibiting strong water absorption and water retention properties. Starch is a natural, environmentally friendly polysaccharide. Starch-based hydrogels have attracted widespread attention due to their favorable biocompatibility, strong biodegradability, and excellent solvent absorption capacity. This review briefly describes common starch modification methods. Subsequently, the preparation of starch-based hydrogels is summarized from three perspectives: chemically cross-linked starch-based hydrogels, physically cross-linked starch-based hydrogels, and double-cross-linked starch-based hydrogels. Furthermore, the application progress of starch-based hydrogels in biosensors, medical dressings, drug delivery carriers, tissue engineering scaffolds, agricultural soil protection, and other fields is introduced. Finally, in view of the existing challenges, future development directions for starch-based hydrogels are proposed.